A Study on Fixed Circles in $ φ $-Metric Spaces - Abhishikta Das; Tarapada Bag (Sahand Communications in Mathematical Analysis)
Our present work is the extension of the line of research in the context of $φ$-metric spaces. We introduce the notion of fixed circle and obtain suitable conditions for the existence and uniqueness of fixed circles for self mappings. Additionally, we present some figures and examples in support of our results.